Two-Term Differential Equations with Matrix Distributional Coefficients - Konstantinov, O.O. (Український математичний журнал, 2015)
We propose a regularization of the formal differential expression l(y) = iⁿy⁽ⁿ⁾(t) + q(t)y(t), t ∈ (a, b), of order n > 2 with matrix distribution q.